Parasites in food chains - Roesel, Kristina; Grace, Delia (International Livestock Research Institute, 2015)
While in high-income countries, the majority of people die from non-communicable, chronic conditions, nearly 40% of deaths in developing countries are among children under 15 years. Diarrhoea is among the top 10 leading causes of death and many cases are caused by pathogens transmitted in food and water supplies. This paper introduces major representatives of foodborne parasites and aims to show why they are no longer a public health concern of low-income countries only. Approaches used in assessing and managing the risk of foodborne parasitoses will be presented.